Tips On Choosing Attractive Packaging For Soap Products Made In Residential Communities - Fajar Ramadhan (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
The development of local products, such as soap made in residential communities, has great potential to improve the economy and creativity at the community level. However, one of the challenges often faced is unattractive and uneconomical packaging. Therefore, this service activity aims to provide training to residential communities in choosing attractive and economical packaging for their soap products. The main objectives of this service activity are; 1) Increasing housing society's understanding of the importance of attractive and economical packaging in marketing soap products. 2) Provide practical guidance in choosing the type of packaging that suits their soap products. And 3) Encouraging residential communities to develop creativity in designing their own product packaging. This service activity will be carried out through a series of interactive training and workshops involving the housing community. The methods used include counseling sessions on the importance of product packaging, demonstrations on the selection of materials and economical packaging designs, packaging design workshops to encourage creativity and group discussions to share experiences and ideas. The results of the Community Service Activity show that participants have a better understanding of the importance of attractive and economical packaging. Then participants can choose the appropriate type of packaging for their soap products, resulting in an increase in the design of soap product packaging, which will help increase product attractiveness and sales.